Etiological Risk Factors Profile of Arterial Ischemic Stroke in Children at A Tertiary Care Children’s Hospital - Naveed Anjum, Muhammad Yousuf, Zia Ur Rehman, Faisal Zafar, Irum Aslam, Hafiz Muhammad Ishfaq (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the etiological risk factors of arterial ischemic stroke (AIS) in children. Study Design: An observational cohort study. Place and Duration of the Study: Neurology department of “The Children’s Hospital and Institute of Child Health, Multan”, from January 2020 to December 2020. Methods: Children in the age group from one month of age to 12 years with a history of acute onset of focal neurological deficit of upper motor nerve and positive findings on neuroimaging were included in the study. The workup included baseline lab testing, neuroimaging, cardiac evaluation, and cerebro-spinal fluid (CSF) laboratory testing. We used predesigned proforma for recording the patient’s details and the possible etiology of the stroke. Results: In a total of 84 children, 28 (33.3%) were male and 56 (66.7%) were female. Age ranged from 4 months to 11 years with a mean age of 3.4±2.2 years. Etiological risk factors identified in 62 (73.8%) patients and were remained undetermined in 22 (26.2%) patients. The risk factors identified were central nervous system infection arteriopathy in 22 (26.2%), iron deficiency anemia 20 (23.8%), cardiac disorders 11 (13.1%), moyamoya disease in 5 (6.0%), and mitochondrial encephalomyopathy, lactic acidosis and stroke-like episodes in 4 (4.8%) patients. Practical Implications: It is essential to know the etiology of risk factors responsible for AIS as the management and prognosis are directly influenced by them. Conclusion: Infection-associated arteriopathy was the most common etiological risk factor for arterial ischemic stroke in our study population. Keywords: Anemia, arterial ischemic stroke, central nervous system, moamoya.